Himnos Homéricos, edición y traducción de J. B. Torres, Madrid, Cátedra Letras Universales, 2005, 444 pp. (Minerva, 2019)
Review: Himnos Homéricos, edición y traducción de J. B. Torres, Madrid, Cátedra Letras Universales, 2005, 444 pp.